2014
DOI: 10.1016/j.apsusc.2014.08.115
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zr alloying on the mechanical properties, thermal stability and oxidation resistance of Cr–Al–N coatings

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights Addition of Zr to sputtered Cr-Al-N coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The chemical composition of the coatings was accessed by energy dispersive spectroscopy (EDS). CrAlN and CrAlTiN films deposited in previous works of the research group [24,25], with the chemical composition measured by EPMA (Electron Probe Microanalysis), were used as references for the EDS analysis. Scanning electron microscopy (SEM) was used to examine the fracture cross section morphology and thickness of the films.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical composition of the coatings was accessed by energy dispersive spectroscopy (EDS). CrAlN and CrAlTiN films deposited in previous works of the research group [24,25], with the chemical composition measured by EPMA (Electron Probe Microanalysis), were used as references for the EDS analysis. Scanning electron microscopy (SEM) was used to examine the fracture cross section morphology and thickness of the films.…”
Section: Methodsmentioning
confidence: 99%
“…It makes CrAlN coatings limited in industrial applications. Recent studies have demonstrated that the incorporation of various elements such as Nb [ 6 ], Mo [ 7 ], Y [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], Ni [ 22 ], Ta [ 23 , 24 ], Hf [ 25 ], V [ 5 , 21 , 26 , 27 , 28 , 29 ], Zr [ 13 , 15 , 30 , 31 ], Ti [ 21 , 32 , 33 , 34 , 35 ], Si [ 36 ], and B [ 37 ] can enhance the comprehensive properties of coatings. For example, alloying element with Y has been reported to enhance the thermal stability, mechanical properties, tribological performance, oxidation resistance, and corrosion resistance [ 6 , 9 , 13 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cr can form a dense oxide that improves the oxidation resistance of nitride films, whereas Zr forms a porous oxide that may have the opposite effect [21,22]. Other studies have shown that with an increasing amount of Cr and a decreasing amount of Zr, the oxidation resistance of the nitride film could be significantly improved [23,24]. Therefore, we proceeded to increase the Cr content and decrease the Zr content to improve the high-temperature applicability of the film.…”
Section: Introductionmentioning
confidence: 99%